The Influence of Financial Literacy and E-Commerce on Jambi Batik Business Performance in Danau Teluk District Jambi City - Hanif, Ikhdan Fatih; Kusumastuti, Ratih; Touriano, Derist (Asosiasi Dosen Akuntansi Indonesia, 2023)
This consideration looks to investigate how money-related proficiency and engagement in e-commerce affect the execution of Jambi Batik businesses within the Danau Teluk Locale of Jambi City. Utilizing a quantitative approach, essential and auxiliary information was utilized from 27 Jambi batik trade members within the Danau Teluk Subdistrict. Information collection included Likert scale surveys, and investigation consolidated Legitimacy and Unwavering quality Tests, R-Square tests, and Speculation Testing with Bootstrapping through the SmartPLS 3.0 Program. Comes shows a positive and critical relationship between money-related Education and Commerce Execution, as well as a critical impact of E-Commerce on trade execution